Legal Presumptions of Reconciling Family Life and Work in the Baltic Countries - Grigužauskaitė, Snieguolė; Skučienė, Daiva (Socialinė teorija, empirija, politika ir praktika, 2019)
[full article and abstract in Lithuanian; abstract in English]One of the main institutions for the welfare of citizens is the family, which acts as a social unit under certain informal and formal rules. In a society, the functioning of a family is best described using institutional theory, which is defined by such terms as organization, behaviour, order, rules. The rules and order are based on the laws that help family members make decisions and function in society while maintaining the integrity of their institution. During the recent decades, the family, as a social unit, has undergone a relatively strong process of deinstitutionalization, which leads to new, major challenges across the European Union. One of the key challenges is the reconciliation of family life and work, which is crucial. In order to manage setbacks, a legal framework is being improved, the content of which varies according to many different aspects in each EU country, while the EU’s objectives and recommendations are the same for all countries. Therefore, there is a need to assess whether different legal instruments create equal or at least similar conditions for family life and work harmonisation. On this basis, the purpose of the study is to compare the favorable work conditions for parents of children under the age of 3 that are provided in the legislation of the Baltic States. To achieve the purpose of the research, the study focuses on these objectives: the analysis of scientific literature based on institutional theory, the analysis of legal acts regulating employment relationship in the Baltic countries, and the laws and data taken from the 2017 MISSOC (Mutual Information System on Social Protection) database. A thematic analysis of the legislation of working conditions, relevant from September to October 2018, was chosen for the purposes of this study. The topics of the legal acts analysis have been formulated on the basis of law groups. The results of the study show that the Baltic countries mainly focus on business trips, breastfeeding breaks, guaranteed paid, free and extra annual leave, protection against harmful working conditions and the termination of contracts for legal regulation. Topics that regulate the least exceptional conditions in the Baltic countries are recruitment, work during weekends and public holidays, work schedule flexibility, remote working.
Keywords: family; work; reconciliation; legal presumptions; institutionalization